Bài 1:
[TEX]a)P=\frac{7\sqrt{x}+1}{x+5\sqrt{x}+4}-\frac{2\sqrt{x}-3}{\sqrt{x}+4}-\frac{\sqrt{x}-1}{\sqrt{x}+1}[/TEX]
[TEX]=\frac{7\sqrt{x}+1}{(sqrt{x}+1)(sqrt{x}+4)}-\frac{2\sqrt{x}-3}{\sqrt{x}+4}-\frac{\sqrt{x}-1}{\sqrt{x}+1}[/TEX]
[TEX]=\frac{7\sqrt{x}+1-(2\sqrt{x}-3)(sqrt{x}+1)-(sqrt{x}-1)(sqrt{x}+4)}{(sqrt{x}+1)(sqrt{x}+4)}[/TEX]
[TEX]=\frac{7\sqrt{x}+1-2x+sqrt{x}+3-x-3\sqrt{x}+4}{(sqrt{x}+1)(sqrt{x}+4)}[/TEX]
[TEX]=\frac{-3x+5\sqrt{x}+8}{(sqrt{x}+1)(sqrt{x}+4)}[/TEX]
[TEX]=\frac{-(sqrt{x}+1)(3sqrt{x}-8)}{(sqrt{x}+1)(sqrt{x}+4)}[/TEX]
[TEX]=\frac{8-3sqrt{x}}{sqrt{x}+4}[/TEX]
[TEX]b)P=\frac{8-3sqrt{x}}{sqrt{x}+4}[/TEX]
[TEX]=\frac{-12-3sqrt{x}+20}{sqrt{x}+4}[/TEX]
[TEX]=\frac{-3(sqrt{x}+4)+20}{sqrt{x}+4}[/TEX]
[TEX]=-3+\frac{20}{sqrt{x}+4}[/TEX]
[TEX]P \in Z[/TEX] \Leftrightarrow [TEX]sqrt{x}+4 \in[/TEX] [TEX]{ \pm1;\pm2;\pm4;\pm5;\pm10;\pm20}[/TEX]
\Leftrightarrow [TEX]sqrt{x} \in {0;1;6;16}[/TEX]
\Leftrightarrow [TEX]x \in {0;1;36,256}[/TEX]